Postoperative Radiation Therapy Is Associated with Longer Overall Survival in Completely Resected Stage II and III Thymoma—An Analysis of the International Thymic Malignancies Interest Group Retrospective Database. Issue 10 (October 2016) - Rimner, Andreas; Yao, Xiaopan; Huang, James; Antonicelli, Alberto; Ahmad, Usman; Korst, Robert J.; Detterbeck, Frank; Gomez, Daniel R.
ABSTRACT : Objectives: : The aim of this study was to determine whether postoperative radiation therapy (PORT) is associated with an overall survival (OS) benefit in patients with completely resected Masaoka or Masaoka‐Koga stage II and III thymoma. Methods: : All patients with completely resected (R0) stage II or III thymoma were identified in a large database of the International Thymic Malignancy Interest Group. Clinical, pathologic, treatment, and follow‐up information were extracted. OS was the primary end point. A univariate analysis using the log‐rank test was performed, and a multivariate Cox model was created to identify factors associated with OS. Results: : Of 1263 patients meeting the selection criteria, 870 (69%) had stage II thymoma. The WHO histologic subtype was A/AB in 360 patients (30%) and B1/B2/B3 in 827 (70%). PORT was given to 55% of patients (n = 689), 15% (n = 180) received chemotherapy, and 10% (n = 122) received both. The 5‐ and 10‐year OS rates for patients having undergone an operation plus PORT were 95% and 86%, respectively, compared with 90% and 79% for patients receiving an operation alone ( p = 0.002). This OS benefit remained significant when patients with stage II ( p = 0.02) and stage III thymoma ( p = 0.0005) were analyzed separately. On multivariate analysis, earlier stage, younger age, absence of paraneoplastic syndrome, and PORT were significantly associated with improved OS. Conclusions: : We observed an OS benefit with the use of PORT in completely resected stage II and III thymoma. In the absence of a randomized trial, this represents the most comprehensive analysis of individual patient data and strong evidence in favor of PORT in this patient population.